Modeling of Mass Transfer Coefficient in Rotating Biological Contactor with Perforated Discs (RPBC) - Mohammed, Alaa Kareem (Al-Khwarizmi Engineering Journal, 2015)
Abstract In order to make an improvement associated with rotating biological contactor (RBC), a new design of biofilm reactor called as Rotating perforated disc biological contactor (RPBC) was developed in which the rotating discs are perforated. The transfer of oxygen from air to wastewater was investigated. Mass-transfer coefficient (KLa) in the liquid phase was determined by measuring the rate transfer of oxygen. A laboratory scale of (RPBC) consisted of a semicircular trough was used with a working capacity of 40 liters capacity of liquid. Synthetic wastewater was used as a liquid phase, while air was used as a gas phase. The effects of many parameters on the liquid phase mass transfer coefficient (KLa) were investigated. These parameters are; the disc rotational speed (N), the pore diameter (d) and clearance between the discs(C). It was found that the value of KLa was increased as the rotation speed (N) increased, and as the diameter of the pores in the disc (d) increased. While the values of (KLa) was decreased continuously with increasing the clearance(C). Suitable correlation was developed for estimating mass transfer coefficient (KLa) in this type of bioreactor. Keywords: Rotating biological contactor, Mass transfer coefficient, Wastewater treatment.